2017
DOI: 10.22190/fueo1604365s
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of Total Quality Management Adoption by Smes in Nigeria

Abstract: Abstract. This study focused on Total Quality Management (TQM) adoption by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Several studies have shown that it is possible for SMEs to adopt TQM practices with a fairly high degree of success (O'Neill et al, 2016;Herzallah et al, 2014). Sule et al (2017) examined and analyzed the consequences of adopting TQM practices in Nigeria's SMEs and have obtained similar results. Hence H03 is in agreement with the existing literature.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Several studies have shown that it is possible for SMEs to adopt TQM practices with a fairly high degree of success (O'Neill et al, 2016;Herzallah et al, 2014). Sule et al (2017) examined and analyzed the consequences of adopting TQM practices in Nigeria's SMEs and have obtained similar results. Hence H03 is in agreement with the existing literature.…”
Section: Discussionmentioning
confidence: 91%
“…Of late SMEs managers are increasingly adopting TQM practices to gain customer's loyalty. TQM is seen as a preferable way to differentiate their entrepreneurial activities in the hope of achieving a better outcome in an increasingly competitive environment (Sule et al, 2017). TQM was introduced in Japan in early 1980s; it is a management approach that endeavour to improve the quality and productive capacity of business organisations.…”
Section: Tqm Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many SME managers have adopted TQM practices to gain customer loyalty. TQM is a preferred approach to differentiate an SME's activities from its competitors and achieve a better outcome in an increasingly competitive environment (Sule et al, 2017).…”
Section: Tqm Practicesmentioning
confidence: 99%